Development of Digital Economy Teaching Materials: Basic Concepts of Business Intelligence - Achmad Tavip Junaedi; Nicholas Renaldo; Indri Yovita; Kristy Veronica; Jahrizal (First Ciera Publisher, 2023)
This study aims to develop digital economy teaching materials in accordance with the concept of business intelligence. Good and thoroughly structured teaching materials are very important in preparing students to understand and apply concepts in the digital economy, especially business intelligence. This research method is a study of literature, analysis of learning needs, development of teaching materials, and evaluation of the effectiveness of teaching materials developed. A literature study will be conducted to gather information about the latest developments in the field of business intelligence and to study existing teaching materials. This research confirms that the digital economy is an important aspect of the development of today's business world. Advances in digital technology have opened up new opportunities and influenced how business is done, becoming the main foundation for developing digital economy teaching materials. The first recommendation is to develop interactive teaching materials based on digital technology.